Uji Beberapa Konsentrasi Metarhizium anisopliae (Metsch Sorokin) Mengendalikan Walang Sangit (Leptocorisa acuta T.) pada Tanaman Padi Gogo (Oryza sativa L.)” Test of Several Concentrations of Metarhizium anisopliae Metch (Sorokin) Local Isolates to Controlling Rice Seed Bug Pest (Leptocorisa acuta T.) on Upland Rice (Oryza sativa - Amdani Parulian Sidauruk; Hafiz Fauzana (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The main obstacles to upland rice is the attack of rice seed bug pest(Leptocorisa acuta T.).These pests attack by sucking mature rice grains at the time of milk, causing grain becomes empty. Environmental pest control was offered using the biological control of the fungus Metarhizium anisopliae Metsch (Sorokin). The aim of the study was to obtain the best local isolate concentration of the entomopathogenic fungi Metarhizium anisopliae in controlling the rice seed bug pest(Leptocorisa acuta T.) pest in upland rice.The research has been implemented in the experimental garden (green house), Faculty of Agriculture, University of Riau which from January to April 2020. The research is prepared using a completely randomized design (CRD) with 5 treatments and 4 repeat, namely the concentration of Metarhizium anisopliae 0, 15, 30, 45 and 60 g l-1 distilled water.The observed parameters are, morphology changes and behavior, the start time of the death (hours), lethal time 50 (hours), daily mortality (%), total mortality (%), temperature and humidity. The results showed that the concentration of 60 g l-1 distilled water was the best concentration in controlling nymphs of Rice Seed Bug Pestwith an initial time of death of 90 hours, LT50 174.25 hours after application and a total mortality of 90%.Keywords: Oryza sativa L., Leptocorisa acuta T., Biological Control, Metarhizium anisopliae Metsch (Sorokin), Concentration